Feasibility and effects of a decision aid about fertility preservation. (3rd April 2017) - Garvelink, Mirjam M.; ter Kuile, Moniek M.; Louwé, Leoni A.; Hilders, Carina G.J.M.; Stiggelbout, Anne M.
Abstract: This paper reports on the feasibility and preliminary effects of a decision aid (DA) about female fertility preservation (FP). We conducted a pilot multicentre randomized controlled trial of women with breast cancer aged 18–40 who were randomized to brochures or the DA. Over 18 months, 62 women were eligible, of which 42 were invited by their healthcare provider (74%) to participate in the study. A total of 36 women signed up for participation and 26 (72%) were randomized to brochures ( n  = 13) or the DA ( n  = 13). In both groups, many women (87%) read the brochures and eight women used all available brochures. In the intervention group, 7/13 women logged in to the DA. Women who received brochures had slightly less decisional conflict, whereas knowledge improved in both groups. Our results indicate that both brochures about FP and a detailed DA have beneficial effects with regard to knowledge, but the DA seemed to introduce slightly more decisional conflict (DC) than the brochures. Although we encountered challenges with recruitment, our design and measurements seem feasible and the effects of the information materials seem promising, hence justifying conducting a larger study.